2020
DOI: 10.1016/j.ijso.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bilateral ilioinguinal-iliohypogastric nerve block versus transverses abdominis nerve block for postoperative pain management for parturient undergoing elective cesarean section in Dilla University Referral Hospital, Ethiopia. A randomized controlled trial

Abstract: Background: Pain is one of the most common complaints and causes of distress in the perioperative period. The postoperative pain after cesarean section is believed to be of mild to moderate intensity lasting for up to 72 h. Apart from patient preferences, several factors affect choices of analgesia in a resource-limited setting like Ethiopia. Availability of resources, trained manpower, and inter-individual variation in pain threshold was among the factors affecting analgesia choices. Thus, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Even though the time to first rescue analgesia request for TAP block is 14.97 more than the IL/IH block, there is no statistically significant difference between the blocks. In line with our study primary studies found that the time to first rescue analgesia request has no statistically significantly different between groups [ 15 , 17 ]. This might be due to their comparative effectiveness in analgesic duration.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Even though the time to first rescue analgesia request for TAP block is 14.97 more than the IL/IH block, there is no statistically significant difference between the blocks. In line with our study primary studies found that the time to first rescue analgesia request has no statistically significantly different between groups [ 15 , 17 ]. This might be due to their comparative effectiveness in analgesic duration.…”
Section: Discussionsupporting
confidence: 90%
“…The time to first analgesic request among the included studies varied from 409 ± 206 min [ 18 ] to 1327 ± 960 min [ 17 ] in the TAP group while it varied from 300 ± 204.44 min [ 19 ]to 1504 ± 834 min [ 17 ] in IL/IH group. Regarding study design, three studies employed an RCT [ 15 , 18 , 19 ] and the remaining two were cohort studies [ 16 , 17 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 114 trials (8730 women) in our final network analysis, 73 (64%) of which reported the primary outcome of morphine equivalent dose in the first 24 postoperative hours for 5126 (59%) women (Fig. 1 and online Supporting Information, Table S1) [14–127]. Placebo vs. transversus abdominis plane injection in 11 trials was the most common direct comparison.…”
Section: Resultsmentioning
confidence: 99%